Do Intellectual Capital and Corporate Reputation Matter to Firm Value Enhancement: The Mediating Role of Financial Performance - Febriantina Istiqomah, Dyah; Metha Nurfitriasih, Dyah; Dwi Candra, Dela (DINASTI RESEARCH, 2024)
This study examines the effect of intellectual capital and corporate reputation on firm value by mediating financial performance. Non-physical capital of the firm, such as intellectual capital and corporate reputation, that is considered good, becomes a positive signal for stakeholders so that it can affect the firm's high value through good financial performance. The research was conducted using a quantitative approach. The research analysis unit comprises food and beverage sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2022. The research sample of 23 companies was selected using the purposive sampling method, so the total research observations were 92 observations for four years. Data collection was carried out using documentation techniques, including data analysis using panel data regression analysis. The Sobel test was conducted to determine whether mediation occurred or not. The analytical tool used is Eviews 12 Enterprise software. The study's results provide evidence that intellectual capital and corporate reputation can indirectly affect firm value through the mediation of financial performance. The form of mediation that arises is full mediation.